Serum levels of apelin, salusin-alpha and salusin-beta in normal pregnancy and preeclampsia - Simsek, Yavuz; Celik, Onder; Yilmaz, Ercan; Karaer, Abdullah; Dogan, Cagdas; Aydin, Suleyman; Ozer, Ali (Taylor & Francis Ltd, 2012)
Objective: The purpose of this study was to investigate the relationship between the serum apelin, salusin-alpha and salusin-beta levels and preeclampsia. Method: Twenty-one healthy pregnant women (control group) and 48 patients with preeclampsia (study group) were included in the study between August 2010 and February 2011. Serum apelin, salusin-alpha and salusin-beta levels of the groups were compared. Results: The patients in the study group were divided into two categories: mild preeclampsia and severe preeclampsia. The mild preeclampsia group consisted of 31 patients, and the severe preeclampsia group consisted of 17 patients. Serum salusin-alpha and salusin-beta levels of the control and study groups were not significantly different (p > 0.05). Apelin levels were statistically significantly higher in the study group. No statistically significant difference was detected between the mild and severe preeclampsia groups in terms of the mean serum apelin levels. Conclusion: The serum levels of apelin were higher in the pregnant women with preeclampsia; however, there was no positive relationship between serum salusin-alpha and salusin-beta levels and the disease. Larger prospective studies are needed to validate our findings.
Keywords: Apelin; hypertension; preeclampsia; salusin-alpha; salusin-beta